Автоматизація складання розкладу занять за допомогою програмного забезпечення FossLook - Пастернак, Христина; Морушко, Олександр (Видавництво Львівської політехніки, 2017)
In the theses on open topic of automation of scheduling classes as one of the major challenges faced by in modern education. From the convenience of a composite schedule for both teachers and students largely depends on the effectiveness of the educational process. Are the main stages of decomposition conclusion, analyzed the most likely factors affecting the process of it’s formation. Advantages FossLook software use in the preparation schedule.
Keywords: навчальний заклад; програмне забезпечення; FossLook; автоматизація; розклад занять